Genomic analysis of HPV-positive versus HPV-negative oesophageal adenocarcinoma identifies a differential mutational landscape. Issue 4 (15th October 2015) - Rajendra, Shanmugarajah; Wang, Bin; Merrett, Neil; Sharma, Prateek; Humphris, Jeremy; Lee, Hong Ching; Wu, Jianmin
Abstract : Background: High-risk human papillomavirus (hr-HPV) has been implicated in a subset of patients with oesophageal adenocarcinoma (OAC). We therefore hypothesised that HPV associated OAC may have distinct genomic aberrations compared with viral negative oesophageal cancer. Methods: Whole exome sequencing was performed to explore the mutational landscape and potential molecular signature of HPV-positive versus HPV-negative OAC. Four hr-HPV-positive and 8 HPV-negative treatment-naive fresh-frozen OAC tissue specimens and matched normal tissue were analysed to identify somatic genomic mutations. Data were subjected to cancer driver gene identification and pathway analysis. Results: The HPV-positive cohort harboured approximately 50% less non-silent somatic mutations than the virus-negative patients with oesophageal cancer (1.31 mutations/Mb vs 2.56 mutations/Mb, p=0.048). TP53 aberrations were absent in the HPV-positive OAC group whereas 50% of the HPV-negative patients with OAC exhibited TP53 mutations. HPV-negative cancers were enriched with non-silent mutations in cancer driver genes, but not HPV-positive tumours. Enriched A>C transversions at adenine-adenine (AA) dinucleotide was observed in 5/7 Siewert class I OAC samples but none (0/5) in Siewert class II tumours (p=0.027). Conclusions: These findings demonstrate distinct genomic differences between HPV-positive and HPV-negative OACs indicating different biological mechanisms of tumour formation.